2016
DOI: 10.17795/jhealthscope-35250
|View full text |Cite
|
Sign up to set email alerts
|

Study of Personal Hearing Protection Devices Usage in Kashan Carpet Industry Workers

Abstract: Background: Exposure to noise can result in hearing loss in many industrial workers. In many cases, hearing protective devices (HPDs) are considered as the main protective objects. As a large number of workers in the Iranian carpet weaving industry are usually exposed to noise levels exceeding the permissible exposure limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The level of use and compliance with wearing HPD was influenced by personal factors, such as education, age, and work experience [ 41 ]. Additionally, young adult workers were more willing to use HPD as they tended to listen to their employer’s instructions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The level of use and compliance with wearing HPD was influenced by personal factors, such as education, age, and work experience [ 41 ]. Additionally, young adult workers were more willing to use HPD as they tended to listen to their employer’s instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is still a shortage of empirical evidence on exposure to noise and HPD use among young adults in the United States despite more than 11 million individuals suffering from NIHL [ 50 ]. Several previous studies have suggested that as workers get older, they are more willing to wear HPDs [ 41 , 42 ]. Age was also a significant predictor for interpersonal modeling and situational influences on HPD use [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 17.0% of the respondents have shown poor practices while another 18.0% shown good practices. This is an important point out to be considered in any shared responsibility between them and the employer to know in detail for personal hearing protective included in the law as well as they need to know what are their responsibilities as well in high-noise workplaces (Taban et al, 2016).…”
Section: Discussionmentioning
confidence: 99%